Molecular Characterization of Xanthomonas oryzae pv. oryzae Isolates and its Resistance Sources in Rice Germplasm - Sandhu, Ahmad Faraz; Khan, Junaid Ahmad; Ali, Safdar; Arshad, H M Imran; Saleem, Kamran (PSM Microbiology, 2018)
Bacterial leaf blight (BLB) of rice, the most notorious and horrendous disease of rice, caused by Xanthomonas oryzae pv. oryzae (Xoo) andcontinue to evolve covering more area and rice cultivars. Keeping in view the escalating virulence in pathogen population, current study was conducted to determine the genetic diversity in pathogen population and to search new sources of resistance in rice germplasm. The samples collected during the survey from different rice growing areas of Punjab were provided by the Rice Pathology group of NIAB. Then these samples were plated to isolate and purify the pathogen causing bacterial blight disease Xanthomonas oryzae pv. oryzae. The genetic diversity of the pathogens from different areas of the Punjab was determined through the repetitive DNA element with primers JEL1 and JEL2. During this study, twenty seven (27) varieties/lines were screened for resistance under artificial inoculation conditions against BLB. Plants were artificially inoculated by clipping method with the Xoo culture. After isolation and purification of pathogen, 9 isolates were selected for genetic diversity. DNA-Fingerprinting of 9 local isolates of Xoo generated with IS1112 based primers Jel1and Jel2, reveal great variability among themselves. The dendrogram showed two main groups A and B. In group A isolates 1, 3 and 5 have 86% similarity while in group B isolates 9 and 8 are 100% similar and 90% similar to 7 and isolate 6 is 87% similar to 4. Where isolate 2 is 82% similar to isolates 4,6,7,8 and 9. In comparison of group A and B they are 65% similar to each other. In search of resistance source against BLB, none of the variety/line out of 27 was found immune, highly resistant, resistant or moderately resistant to bacterial leaf blight disease. Only one variety/line was moderately susceptible, five were susceptible and twenty one were highly susceptible to BLB disease. The results of this study seem to be very helpful for deploying effective management of BLB disease. The information can be utilized in controlling the bacterial leaf blight disease in Pakistan that can save the economic and production losses of rice crop that are increasing every year.